Integration of Expected Spoilage Cost in Calculating the Cost of Goods Sold in Perishable Culinary MSMEs: A Case Study of Kang Dani's Siomay Sales in Mojokerto - Nayola Isti; Alfan Syihabul; Cipta Abyan; Nuril Mirza; Michiko Dinary; Darlin Aulia (PT. Maju Malaqbi Makkarana, 2026)
Culinary MSMEs with perishable products face challenges in managing production costs due to the presence of unsold products, which are often not included in determining the Cost of Goods Sold (COGS). This study aims to analyze the application of the full costing method by integrating Expected Spoilage Cost into the COGS calculation at Siomay Kang Dani MSME and evaluate its impact on business profitability. The study used a descriptive quantitative approach with a single case study method. Data were obtained through interviews, direct observation, and documentation related to production costs and the number of unsold products. The results show that the conventional COGS of Rp7,665 per portion increased to Rp8,975 per portion after incorporating the Expected Spoilage Cost of Rp591,240 per month. The integration of spoilage costs results in a more realistic cost calculation because it considers losses due to leftover products. A sensitivity analysis also shows that increasing spoilage levels leads to an increase in COGS and a decrease in profit margins. This study suggests that the application of a modified COGS can help MSMEs set selling prices and manage profitability more accurately